Anteseden Kinerja Bisnis Perhotelan di Kabupaten Banyumas - Syifa Kemala Mukaromah (Business, Accounting and Management Journal, 2023)
A key pillar supporting sustainable competitive advantage is knowledge assets. The purpose of this study is to analyze the impact of COVID-19, that is, the positive impact of human capital, structural capital, relational capital and cost effectiveness on the business activities of hotels in the Baturaden region in the period 2020-2022. The population of this study is all hotels in Baturraden District  of  Banyumas Regency, that is 113 hotels. A random sampling method was used to determine the sample and the sample size was determined to be 72 hotels. The data collection method used  printed questionnaires, which resulted from 53 respondents. The research approach used the quantitative approach. The method of data analysis  was performed by multiple linear regression analysis using  SPSS application 26. The results of the analysis showed that (1) human capital has a positive and significant effect on business activity. (2) structural capital has no effect on business performance and (3) relational capital has a positive  and significant  effect on business performance. (4) Payment authority does not apply to commercial activities. The results of this study show that hotel management can achieve competitive advantages and good business practices by creating added value for hotels.